2021
DOI: 10.1021/acssuschemeng.1c03772
|View full text |Cite
|
Sign up to set email alerts
|

Production Cost and Carbon Footprint of Biomass-Derived Dimethylcyclooctane as a High-Performance Jet Fuel Blendstock

Abstract: Near-term decarbonization of aviation requires energy-dense, renewable liquid fuels. Biomass-derived 1,4-dimethylcyclooctane (DMCO), a cyclic alkane with a volumetric net heat of combustion up to 9.2% higher than Jet A, has the potential to serve as a low-carbon, high-performance jet fuel blendstock that may enable paraffinic bio-jet fuels to operate without aromatic compounds. DMCO can be produced from bio-derived isoprenol (3-methyl-3buten-1-ol) through a multistep upgrading process. This study presents deta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Therefore, nickel-based catalysts are likely preferred for the hydrogenation of the isoprene cyclodimers. 51 However, the higher pressures and temperatures required to obtain complete conversion may partially offset the lower catalyst cost.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, nickel-based catalysts are likely preferred for the hydrogenation of the isoprene cyclodimers. 51 However, the higher pressures and temperatures required to obtain complete conversion may partially offset the lower catalyst cost.…”
Section: Resultsmentioning
confidence: 99%
“…The CI of SAF derived from corn grain ethanol is 26% lower than the CI of petroleum jet fuel, and several cellulosic and advanced biomass feedstock have potential emission reductions of 33%–91% . For that reason, many previous studies have focused on developing the cellulosic pathways to SAF production. …”
Section: Introductionmentioning
confidence: 99%
“…26,27 Interestingly, the hydrogenated [4+4] dimers of isoprene have better fuel properties compared to conventional jet fuels (Jet-A), and a life-cycle assessment and technoeconomic analysis showed that the process can be further improved to reduce cost and emission to compete within the sustainable aviation fuel sector. 28 The [2+2] oligomerization of isoprene was not selective for dimers since also trimers and tetramers were formed in significant amounts.…”
Section: Introductionmentioning
confidence: 99%